Seeding as a restoration technique for a rare prairie plant: an 11‐year field experiment with Asclepias meadii. Issue 5 (23rd November 2021) - Hoffpauir, Alexandria N.; Reed, Aaron W.; Kettle, W. Dean; Roels, Steven M.; Alexander, Helen M.
Abstract : Prairie restorations typically differ from remnant prairies in forb composition; long‐lived, late‐successional plants are often missing. To study establishment of such species, we set up a field experiment where seeds of the threatened, long‐lived Asclepias meadii were sown individually into the field with initial fire and soil disturbance treatments. We returned each year for 11 years to record the presence/absence, size, and reproduction of each plant. Individual plants were sometimes observed 1 year, not observed a subsequent year, and then observed again. We therefore analyzed survival data with mark‐recapture models and found that the probability of a seed germinating and the resulting plant surviving for 11 years was 0.057 (5.7%). Probability of detection was approximately 0.80, suggesting that we did not observe all living plants. Vegetative dormancy, herbivory on above‐ground parts, and observer error could all be responsible. We found no relationship between plant survival and the initial burn/disturbance treatment or previous year precipitation. Plants that were observed in the last study year were individuals that had, on average, greater size in earlier years. Three plants produced flowers and two produced fruit; we believe such reproductive success has not been previously documented for seed of A. meadii sowed into a restoration site. Our restoration study dovetails with the more typical plant community restoration research. In such studies, seeds of many species are sown, but often the late successional species do not establish. We show the value of detailed multiyear monitoring to determine the fate of such plant introductions.